Oral Testimonies on Sai Baba (Edizioni Ca’ Foscari – Venice University Press, 2026)
The interviews and audio recordings comprised in this volume are the outcome of a field research to Maharashtra and Andhra Pradesh which took place in October-November 1985 for the preparation of the Author’s BA thesis on the life and teachings of the Indian saint Sai Baba of Shirdi (d. 1918), discussed at the Ca’ Foscari University of Venice in June 1987 (Un maestro dell’India moderna: il Sāī Bābā di Śirḍī. L’uomo, l’ambiente, gli insegnamenti). The conversations of each day are preceded by excerpts from the Authorʼs diary. These testimonies record the words of various people in the village of Shirdi and other locales, among whom are the last old men who knew Sai Baba: Balaji Pilaji Gurav, Bappaji Lakshman Ratna Parke, Martanda Mhalsapati, Pandharinath Bhagavant Gonkar, Tukaram Raghujiv Borawke, and Uddhavrao Madhavrao Deshpande. While in Shirdi the Author was also able to interview Uttamrao Patil, son of Tatya Kote Patil, and in Mumbai he had the privilege of meeting Swami Ram Baba, who first met the saint in 1914. Taken altogether, these conversations are primary sources for the study of Sai Baba and may help to contextualize Shirdi as a pilgrimage place in the mid-1980s.